The birth of doubt : confronting uncertainty in early rabbinic literature - Halbertal, Moshe (Brown Judaic studies, 2020)
"In the rabbinic laws in the Mishnah, the Sages constructed an entire field of instructions concerning how to behave in situations of uncertainty ranging from matters of ritual purity, to lineage and marriage, to monetary law, and to the laws of forbidden foods. Reflecting on the weight assigned to different possible errors that could be made and examining the norms of uncertainty opens a window for understanding the early rabbinic that reflected rules aimed not at avoidance but rather at dwelling in the midst of uncertainty, thus rejecting sectarian isolationism meant to minimize a community's friction with uncertainty"--